EFEKTIVITAS PELAKSANAAN TUGAS DAN WEWENANG KEPALA DESA KARYA INDAH KECAMATAN TAPUNG KABUPATEN KAMPAR - Mutari, Elita Gusfa; Yuliani, Febri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The village is the unity of the legal community who have boundaries that limit the authority to regulate and manage the interests of the local community. Based on the origin and local customs are recognized and respected in the governance system of the Republic of Indonesia. The village head position as head of government in the village of village chief has the duty and authority to carry out most of the affairs of the village households to the village chief must melaksananakan its duties and powers by either a way to involve all communities in all activities. This aims to determine the effectiveness of the execution of tasks and authority of the village chief and the factors that affect the execution of tasks and authority of the Head of the Village District of Tapung Beautiful work Kampar district. The theory used in this study is the theory put forward by Winardi effectiveness, effectiveness of Implementation, as well as the duties and authority of the chief. This study uses qualitative research methods to study descriptive data. In collecting the data, the researchers used a technique of observation, indepth interviews, documentation, and literature study. By using key informants as a source of information. The results of a descriptive qualitative data analysis found that the effectiveness of the execution of tasks and authority of the Head of the Village Beautiful work had not been effective. It can be seen from not achieving the objectives and the expected rate of change in the program. In this research note the factors that influence the effectiveness of the execution of tasks and authority of the Head of the Village Beautiful work, among others, a lack of human resources, abilities and skills as well as the village chief factor derived from the public.Kata Kunci : Effectiveness, implementation, Duties and Powers.